Macroalgal composition and its association with local hydrodynamics in the Laje de Santos Marine State Park, southwestern Atlantic, São Paulo, Brazil - Renato Rocha Jorge; Joseph Harari; Mutue Toyota Fujii (Brazilian Journal of Oceanography, 2012)
The Laje de Santos Marine State Park (LSMSP), located in southeastern Brazil, is the only marine park in São Paulo State. This conservation unit has been established as a protected area of high biological diversity. Despite its importance for the conservation of the marine biota, little is known about the park's seaweed flora. The objectives of this study were as follows: to furnish increased knowledge of the composition of the macroalgae in the Park area; to relate the area's macroalgal composition to the presence of an important water mass in the region, the South Atlantic Central Water (SACW); and to investigate the possible influence of the Port of Santos on the composition of the macroalgae of the LSMSP. This study registered 31 new records for the LSMSP, 11 for São Paulo State, four for Brazil, one for the western Atlantic and one for the South Atlantic Ocean, in addition to the possible occurrence of one new species of Osmundea (Rhodomelaceae) and one new genus belonging to Ceramiaceae. The taxonomic composition of the macroalgae had a direct correlation with the arrival of the SACW in the summer-fall season. The SACW generated a strong thermocline and increased the supply of nutrients in the water column. Hydrodynamic and dispersion modeling analyses suggested that the Port of Santos influenced the composition of the LSMSP phycoflora. O Parque Estadual Marinho da Laje de Santos (PEMLS), localizado no sudeste do Brasil, é o único parque marinho do litoral paulista. Essa unidade de conservação foi classificada como de "alta diversidade biológica". Apesar da sua importância para a preservação da biota marinha, pouco é conhecido sobre a flora de macroalgas do Parque. Os obejtivos deste estudo foram: aumentar o conhecimento da composição de macroalgas na região do PEMLS; relacionar tal composição com a presença de uma importante massa d'água na região, a Água Central do Atlântico Sul (ACAS); e verificar uma possivel influência do Porto de Santos na composição ficológica do Parque. O presente estudo registrou 31 novas ocorrências para o Parque, 11 para o estado de São Paulo, quatro para o Brasil, uma para o Atlântico Ocidental e uma para o Atlântico Sul, além de duas prováveis novas ocorrências para a ciência: uma espécie de Osmundea (Rhodomelaceae) e um gênero pertencente e Ceramiaceae. Segundo os dados encontrados, a composição de macroalgas tem uma correlação direta com a presença da ACAS no período de verão-outono. Essa frente térmica profunda promove a formação de uma forte termoclina e aumenta o aporte de nutrientes na coluna d'água. Análises dos modelos hidrodinâmico e de dispersão sugerem que o Porto de Santos pode influenciar a composição ficológica do local.